The Crisis in the Emerging Markets - Impact of the Subprime Crisis on the Indian Stock Markets - Bhammer, Harsh (2009)
The world has seen one of the worst financial disasters in history, which started of as the subprime crisis turned into something much greater, a ̳Global Meltdown‘. The aim of this dissertation is to assess the impact of the subprime crisis on the Indian Stock Markets. Two methods of research were used- first; an open questionnaire seeking the views of the industry experts on the subprime crisis and its effect on the Indian Stock Markets and second; a regression analysis using Ordinary Least Squares to assess the impact of the Dow Jones Industrial Average (DJIA) and the Net Foreign Institutional Investors (FII) flows on the movement in the BSE Sensex Index (Bombay Stock Exchange Sensitive Index); starting with the onset of the crisis and the subsisting period when the effects of the crisis continued to be felt at their maximum. This exercise was performed in order to assess whether there was any direct correlation of the subprime crisis with the BSE Sensex.